Distrusting minds, skeptical judgments? No evidence for a trust-truth link - Bertram, Anna-Marie; Lalot, Fanny; van der Werff, Lisa; Greifeneder, Rainer (Frontiers in Psychology, 2025)
IntroductionMany daily situations require rapid judgments about whether information is true or false based on limited information. Prior research has predominantly examined how statement and source characteristics influence these judgments. The present study shifts its focus to individuals’ stable traits, specifically trust propensity, and its role in shaping truth judgments.MethodsAcross three studies considering different social contexts (N = 679), we investigate whether trust propensity (i.e., one’s general tendency to trust others) and the closely related construct of social trust (i.e., one’s perception of others in general as more or less trustworthy) are associated with a greater likelihood of judging various statements as true.ResultsContrary to expectations, linear mixed-effects analyses indicated that neither trust propensity nor social trust had any significant relationship with truth judgments across contexts. Bayesian analyses further indicated strong overall support for the null hypothesis over the alternative.DiscussionThus, this research highlights that, contrary to common-sense belief, trust-related traits may play a relatively minor role in decision-making under uncertainty.